Discurso de ódio e redes sociais digitais: um estudo psicanalítico sobre a errância no espaço digital. - Oliveira, Philippe José de Fontes (2024)
The phenomenon of hate speech permeates society in all domains, regardless of whether it manifests in the concrete or digital realm. In the digital context, however, it stands out due to a dynamic amplified by the reach of networks, which have a structure where a post can reach hundreds or thousands of people regardless of the public relevance of the original author. This can result in extremely harmful effects on an unlimited scale. Furthermore, the structure of digital social networks facilitates the formation of groups of people without deeper connections, allowing the discourse to be echoed and reverberated, increasing the potential for psychological and social harm. Due to experience in the digital environment and observation of how this phenomenon impacts society and, consequently, clinical practice, we find it relevant to conduct a detailed investigation into how this “economy of hatred” occurs and involves individuals. This results in the almost nonexistence of dialogue and, in practice, an attempt to obliterate the other. In search of possibilities for understanding, we rely on Lacanian psychoanalytic theory, especially the lessons from Seminar XXI: “Les non-dupes errent,” which addresses Lacan’s constructions on the Borromean knotting and the wandering of desire, considering the hypothesis of a possible “digital wandering” as a movement where subjects find themselves lost among the signifiers they encounter, making the Real prevalent. Thus, we define the general objective as investigating hate speech on digital social networks, conveyed through a movement that establishes itself in terms of “digital wandering,” adopting Lacanian propositions about hatred and wandering as a theoretical framework. For this investigation, we employ a methodology based on Social Network Analysis (SNA), utilizing information technology software for data collection. With these data in hand, we draw inspiration from Discourse Analysis (DA) to conduct a psychoanalytic observation of the utterances in the posts. In conclusion, we observe that a prevailing Real, in addition to the inflated Imaginary of the networks, leads to a tendency to loosen the Borromean knot, compromising not only the psychic structure of individuals but also their condition as subjects, affecting even the social bond. Furthermore, we find that individuals involved in hate speech fit Freud’s description in “Group Psychology and the Analysis of the Ego” but also exhibit characteristics of a swarm, as defined by Byung Chul Han.